Tackling antimicrobial resistance through two novel methods: repurposing vanoxerine as a novel anti-tubercular drug; and silencing virulence in Pseudomonas aeruginosa through inhibition of PqsR - Grossman, Scott (2018)
The antimicrobial resistance crisis is one which will persist and worsen without intervention. This thesis looks to explore two innovative research areas in order to develop new antibiotics and stem the rise in antibiotic resistance. The first project looked at the potential to repurpose the former central nervous system (CNS) drug candidate vanoxerine into an anti-tubercular compound. Previous work has suggested that vanoxerine acts as a prodrug in mycobacteria and interacts with the monooxygenase enzymes Rv0565c and Rv3518c of Mycobacterium tuberculosis (Mtb). In this work a MIC50 assay was utilised to complete a structure-activity relationship (SAR) study and prove that vanoxerine is hydroxylated in vivo to its active form. Further to this, a global lipid analysis was completed suggesting that when treated with analogues of vanoxerine a lipid biosynthetic pathway was halted, though the lipid itself could not be identified. Although mass spectrometry was employed to identify changes in lipid concentrations at varying concentrations of drug, no trends were clear. However, the mass spectrometry data did indicate that analogues of vanoxerine were also hydroxylated in vivo, furthering the original hypothesis.